CYBER PUBLIC RELATIONS PADA APLIKASI PENGADUAN WARGAKU DALAM PELAYANAN PUBLIK DI KOTA SURABAYA (The Commercium, 2023)
Digitalization era requires Surabaya Government strive to meet socity’s needs for public services. This is shown by the launch of Wargaku application which serves all public problems and aspirations. The utilization of technology in Wargaku is an element of the cyber public relations approach. Claiming a response speed of 1x24 hours, this application has received a high response of public participation. Although considered successful, based on the public satisfaction survey there are still several things that need further attantion such as responsiveness, substance, appearance, convenience and interference with the application. In addition, external factors such as socialization and paradox of choices to media that have almost same role also confuse the public. The purpose of research to describes cyber public relations of Wargaku complaint application on public services at Surabaya City. This type of research is descriptive qualitative with a case study method. This research uses data collection techniques in the form of in depth interview and documentation. Then, the analyzed using an interactive data analysis model. The results obtained from the application of cyber public relations have been reflected in the Wargaku as an effort to provide good public services. However, the aspects of message transformation and reach still need to be improved.